Additive manufacturing of smart polymeric composites: Literature review and future perspectives - Hamid Ikram (14779036) (2023)
The latest developments in smart systems for improved human lives with advanced biomedical devices have evolved out of multi-disciplinary scientific studies, including medicine, biology, material sciences, design, manufacturing, artificial intelligence, microelectronics, and so forth. The growth of such intelligent systems is primarily possible with innovative materials, which demonstrate the response to various external stimuli like temperature, heat, moisture, light, electromagnetic field, and chemical alteration. Such materials have been recently fabricated using different additive manufacturing techniques to devise personalized unique, complex, and novel structures that can adjust to external conditions over time and are specifically attributed to 4D printing. Novel materials that can further improve such systems continued to be explored and employed. This review paper investigates the additive manufacturing of functional polymer nanocomposites, which offer compliant structures with flexible manufacturing processes with high strength, low cost, and long-term stability. This study aims to deliver a comprehensive and deep understanding of the latest developments in materials, design, manufacturing, fundamental mechanisms involved, and future possibilities in this area of research. Other Information Published in: Polymer Composites License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/pc.26948